2018
DOI: 10.22201/fpsi.20074719e.2018.2.03
|View full text |Cite
|
Sign up to set email alerts
|

Motivación y Personalidad en la Elección de Carrera: Turismo y Negocios Internacionales

Abstract: En la elección de carrera intervienen particularidades de la personalidad, la familia y el entorno social, además de efectos de carácter económico e institucional en razón de las posibles repercusiones relacionadas con la demanda educativa en Universidades públicas. El objetivo del estudio consistió en indagar sobre la motivación en la elección de carrera y las diferencias en las características de personalidad que tienen los estudiantes de las carreras en Negocios Internacionales y Turismo en la Universidad d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
0
4
0
4
Order By: Relevance
“…However, it was concluded that the social support that students perceive from their family is the most significant correlation. When comparing the results of this study with those found in similar investigations (Cruz- Barba & Silva-Gutiérrez, 2018;Farías-Martínez et al, 2016;García-Sedeño et al, 2009), it is important to take into account that the size of the effect of the personality factors on the level of satisfaction with the career was small in the trait of responsibility and medium in the case of neuroticism. Additionally, unlike similar studies, in the present, career groups were taken into account instead of academic areas.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…However, it was concluded that the social support that students perceive from their family is the most significant correlation. When comparing the results of this study with those found in similar investigations (Cruz- Barba & Silva-Gutiérrez, 2018;Farías-Martínez et al, 2016;García-Sedeño et al, 2009), it is important to take into account that the size of the effect of the personality factors on the level of satisfaction with the career was small in the trait of responsibility and medium in the case of neuroticism. Additionally, unlike similar studies, in the present, career groups were taken into account instead of academic areas.…”
Section: Discussionmentioning
confidence: 53%
“…In addition, the main results of the study show discrepancy with those of other investigations. For example, Cruz- Barba and Silva-Gutiérrez (2018) were based on Holland's model and found that international business and tourism students fit the entrepreneurial profile, similarly, Garcia- Sedeño et al (2009) divided their student population into two groups (sciencestechnology and humanities-social sciences) and obtained significant differences between them, and finally Guzmán-González et al (2020) studied a sample of psychology students and found that they share traits such as instability emotional and detachment from social norms. When taking into account the satisfaction variable in order to know its interaction with the personality of the students, it was found that satisfied university students are more responsible and present lower levels of neuroticism than dissatisfied students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the four interviews was carried out using a qualitative methodology with the WebQDA qualitative analysis software [65] in order to categorize the internal and external motivating factors that led these four subjects to decide on their studies and professions with the same categories used in previous studies [20,[66][67][68]. Consequently, our results will be comparable with the data from those studies.…”
Section: Discussionmentioning
confidence: 82%
“…Los resultados expuestos también evidencian que la población investigada eligió la carrera por motivaciones personales como el gusto por el espacio de trabajo, las personas con las que se desenvolverá como son niños y adolescentes y la vocación con la carrera, estos resultados coinciden con lo expresado por Araya (2019), quien encontró valores significativos en el factor vocación con la carrera. Al respecto Cruz & Silva (2018), manifiestan que la información vocacional es relevante en la elección de la carrera universitaria. Por otra parte, es importante destacar que la población investigada considere que tiene las habilidades sociales suficientes para desempeñarse en la carrera además que expresa tener un gusto por el trabajo con niños y/o adolescentes, esto coincide con Avendaño & González (2012), quienes también encontró este factor como motivo de elección de la carrera de pedagogía.…”
Section: Docencia E Investigación En Educación Superiorunclassified